LIPID NANOPARTICLE-MEDIATED MRNA DELIVERY FOR A NOVEL UNIVERSAL VACCINE AGAINST INFLUENZA VIRUS SUBTYPES - Pradeep, Lakshan; Wijerathna, Kumudu; Perera, Dilshan (Journal of Biomedical and Techno Nanomaterials, 2025)
Influenza viruses continue to pose a major global health challenge due to rapid antigenic drift and shift, which limit the effectiveness of seasonal, strain-specific vaccines. Current vaccine strategies require frequent reformulation and often fail to provide broad and durable protection against diverse influenza virus subtypes. This study aims to develop a lipid nanoparticle–mediated mRNA delivery platform encoding conserved influenza antigens as a novel universal vaccine strategy. An experimental preclinical design was employed, involving in vitro transcription of mRNA, formulation into lipid nanoparticles, physicochemical characterization, and immunological evaluation in animal models. Particle size, encapsulation efficiency, mRNA expression, and stability were systematically assessed, followed by analysis of humoral and cellular immune responses and heterologous viral challenge studies. The mRNA–LNP vaccine exhibited uniform nanoscale properties, high mRNA integrity, and efficient antigen expression. Immunization induced robust cross-reactive antibody responses and strong CD4? and CD8? T-cell activation against multiple influenza subtypes. Vaccinated subjects demonstrated reduced viral loads, attenuated disease severity, and improved survival following heterologous influenza challenge. These findings indicate that lipid nanoparticle–mediated mRNA delivery of conserved influenza antigens represents a promising and adaptable platform for universal influenza vaccination, with significant potential to enhance pandemic preparedness and long-term influenza control.